Arrhythmia during diagnostic cardiac catheterization in pediatric patients with congenital heart disease - Taner Kasar; Ibrahim Cansaran Tanıdır; Erkut Öztürk; Selman Gökalp; Gülhan Tunca Şahin; Mehmet Akın Topkarcı; Yakup Ergül; Alper Güzeltaş (KARE Publishing, 2018)
Objective: Diagnostic and interventional cardiac catheterization procedures for congenital heart diseases (CHD) are becoming increasingly more popular, and arrhythmia is a well-known complication. This study was an evaluation of the incidence and causative agents of arrhythmia and the subsequent treatment strategies applied during cardiac catheterization. Methods: The catheterization data of all of the patients who underwent diagnostic cardiac catheterization for CHD between January 2012 and 2018 at a single center were examined retrospectively. Results: A total of 1316 children underwent diagnostic cardiac catheterization due to CHD. The median age and body weight was 18 months (6 days-21 years) and 9.9 kg (2.2-135 kg), respectively. Patients with ventricular septal defect (281 patients) and those with tetralogy of Fallot (257 patients) represented 2 major groups in the study population. In 93 (7%) patients, arrhythmia developed during cardiac catheterization. Among them, there were 58 (62%) cases of bradyarrhythmia and 35 (38%) cases of tachyarrhythmia. Arrhythmia was classified as low, high, or major, according to the adverse event severity score; the rates were 2.7%, 4.3%, and 1.2%, respectively. In 36 (39%) patients, there was no need for therapy, whereas 57 (61%) required treatment to eliminate the arrhythmia. Treatment modalities included catheter manipulation in 15, pharmacological therapy in 24, and cardioversion in 3 patients. Eleven patients required cardiopulmonary resuscitation. Temporary pacemaker implantation was required in 2 patients, while 2 others underwent permanent pacemaker implantation secondary to catheterization-related arrhythmia. There were no cases of mortality secondary to catheterization-related arrhythmia. Conclusion: Diagnostic cardiac catheterization in CHD may result in various types of cardiac arrhythmias. The proper management of arrhythmias may reduce morbidity and mortality related to cardiac catheterization.